2020
DOI: 10.1007/s00766-020-00330-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling functional requirements using tacit knowledge: a design science research methodology informed approach

Abstract: The research in this paper adds to the discussion linked to the challenge of capturing and modeling tacit knowledge throughout software development projects. The issue emerged when modeling functional requirements during a project for a client. However, using the design science research methodology at a particular point in the project helped to create an artifact, a functional requirements modeling technique, that resolved the issue with tacit knowledge. Accordingly, this paper includes research based upon the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the field of CS education, Naidoo et al (2012) showed how DSR could contribute to innovations and rigor of computing artefacts. Consequently, computer science scholars have been conducting research to either produce artefacts to solve practical problems using the DSR methodology (Benfell, 2020;Leinonen et al, 2016;Oyelere et al, 2018) or to design a theoretical framework that supports the use of DSR in the field (Elragal et al, 2019;Carstensen & Bernhard, 2019;Apiola & Sutinen, 2021). For example, Leinonen et al (2016) in collaboration with the students developed mobile applications to foster students' reflection during classroom learning by using the DSR method.…”
Section: The Design Science Research Methodologymentioning
confidence: 99%
“…In the field of CS education, Naidoo et al (2012) showed how DSR could contribute to innovations and rigor of computing artefacts. Consequently, computer science scholars have been conducting research to either produce artefacts to solve practical problems using the DSR methodology (Benfell, 2020;Leinonen et al, 2016;Oyelere et al, 2018) or to design a theoretical framework that supports the use of DSR in the field (Elragal et al, 2019;Carstensen & Bernhard, 2019;Apiola & Sutinen, 2021). For example, Leinonen et al (2016) in collaboration with the students developed mobile applications to foster students' reflection during classroom learning by using the DSR method.…”
Section: The Design Science Research Methodologymentioning
confidence: 99%
“…DSRM defines the research process and activity flows for presenting, and conducting design science research [18]. In Information Systems, the DSRM is based on the notion model conducted by Takeda (1990) [4], as shown in Fig.…”
Section: Design Science Research Methods In Information Systemsmentioning
confidence: 99%
“…Although its use is often not explicitly mentioned in Software Engineering research, in an analysis of awarded papers in the International Conference on Software Engineering, Engstrom et al [41] showed that most of these studies actually could be classified as DSR although not explicitly using the term. More recently, though, researchers have explicitly used the methodology to tackle problems in software engineering like gamification (e.g., [42]) and requirements (e.g., [43]).…”
Section: Methodsmentioning
confidence: 99%